Analisis Strategi Bersaing Grab Bike Dalam Menciptakan Loyalitas Pelanggan - Budi Ismanto (Prisani Cendekia, 2022)
This research is a qualitative research to examine the implementation of strategy of Grab bike bersahang in creating customer's activity in Jabodetabek area. The focus of this research is how to Grab bike competitiveness in increasing customer loyalty because the more fore the higher the level of online intercommunication ojek (online). The purpose of this research is whether the price , pelayana and products developed by the grab able to provide customer loyalty in Jabodetabek area. This research uses qualitative approach with case study method. The analyzed data are the result of kusioner with the customer, Grab bike driver and penliti sendiri.dan researchers also directly participate berpatispasi activities as a driver to experience things that become complaints from the Grab bike drivers. The results show that Grab bike competing strategy in creating customer aggressive loyalty is utilizing internal strength and taking advantage of external opportunities, but behind it there is an aggrieved that is partner Grab bike, because the more fore the price and bonus offered much different from the previous. may be an internal constraint if it always runs unfairly with the partner (driver). how to overcome it and whether this problem has been resolved or unresolved